Chemical bonding in representative astrophysically relevant neutral, cation, and anion HCnH chains - Bâldea, Ioan (Chinese physics, 2022)
Most existing studies assign a polyynic and cumulenic character of chemical bonding in carbon-based chains relying on values of the bond lengths. Building on our recent work, in this paper we add further evidence on the limitations of such an analysis and demonstrate the significant insight gained via natural bond analysis. Presently reported results include atomic charges, natural bond order and valence indices obtained from ab initio computations for representative members of the astrophysically relevant neutral and charged HC2k/2k + 1H chain family. They unravel a series of counter-intuitive aspects and/or help naive intuition in properly understanding microscopic processes, e.g., electron removal from or electron attachment to a neutral chain. Demonstrating that the Wiberg indices adequately quantify the chemical bonding structure of the HC2k/2k + 1H chains - while the often heavily advertised Mayer indices do not - represents an important message conveyed by the present study.
In der chemischen Formel erscheint das n tiefgestellt
Gesehen am 01.02.2023